Assessment and referral of patients with short stature by primary care physicians in the Arabian gulf region: Current perspectives from a regional survey - Kaplan, W.; Al Amiri, E.; Attia, N.; Al Basiri, I.; Romany, I.; Al Shehri, E.; Al Twaim, A.; Al Yaarubi, S.; Deeb, A. (Frontiers in Pediatrics, 2022)
Children with short stature are frequently referred late to pediatric endocrinologists in the Arabian Gulf region. This is likely a contributing factor to late initiation of treatment despite current evidence suggesting that children with short stature have better outcomes with earlier treatment. This delay in referral could be due to a lack of identification or proper assessment of short stature by front-line physicians. To analyze the assessment and perception of short stature in this group of physicians, an expert group of pediatric endocrinologists developed and disseminated an anonymous online survey of 22 multiple choice questions amongst general pediatricians, pediatric subspecialists, and family medicine physicians in the Arabian Gulf region. Of the 640 respondents, 450 completed the survey (70.3% completion rate). While most surveyed physicians use the correct definition for short stature in children, only 24% reported a consistent use of a wall-mounted stadiometer. Of the respondents, 50% or less would consider referring clinical conditions other than growth hormone (GH) deficiency or idiopathic short stature, 41% would refer a child with short stature as soon as height dropped below the 5th percentile, 57% considered GH a treatment option for short stature, and only 60% consider GH treatment safe. The results of this survey demonstrate knowledge gaps in short stature assessment and referral that need to be addressed through education on short stature amongst target physicians, and lay groundwork for future recommendations to address those gaps in the Arabian Gulf region.